Optimal capacitor allocation in distribution system using particle swarm optimization - Hasan, Ihsan Jabbar; Shamshiri, Meysam; Gan, Chin Kim; Ab Ghani, Mohd Ruddin; Bugis, Ismadi (2013)
In distribution networks, capacitor installation is one of the commonly used methods for reactive power compensation. Capacitor placement and sizing in power system can be applied in multiple objectives and reasons. In this paper, the optimum capacitor placement and sizing has been applied in the distribution network in terms of power losses minimization and voltage profile improvement. The maximum and minimum bus voltage and maximum possible capacitor size are the constraints of optimum capacitor placement and sizing problem which considered as a penalty factor in the objective function. In order to solve the obtained objective function, the Particle Swarm Optimization (PSO) is utilizes to find the best possible capacitor placement and size. The OpenDSS software has been utilized to solve the power flow through Matlab coding interface. To validate the functionality of the proposed method, the IEEE 13-bus test system is implemented and the obtained results have been compared with IEEE standard case and without capacitor case. The result shows that the proposed algorithm is more cost effective and has lower power losses compare to the IEEE standard case. In addition, the voltage profile has been improved, accordingly.